Customer Brand Engagement Pengguna Electronic Payment - Valentino, John; Erdiansyah, Rezi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The use of electronic payments is increasingly widespread. In this case, digital payment users in Indonesia are already quite high and various e-wallet companies are also competing to become leaders in providing digital payment services.) Electronic payments must be trusted for their safety and must also be able to facilitate human activities in using them. Research This study aims to determine the effect of social media marketing and brand trust on customer brand engagement (a case study of electronic payment users). The theory used is the theory of marketing communications, social media, brand trust, and consumer engagement. This research uses quantitative methods. The data collection technique used is by using a questionnaire. The method used is to distribute questionnaires via the Google form by distributing them online to people who have used electronic payments. The population of this study are electronic payment users and the sample used is 100 samples. The results of this study are that Social Media Marketing and Brand Trust have an influence on customer brand engagement in electronic payment users. Penggunaan electronic payment semakin meluas. Dalam hal ini pengguna pembayaran digital di Indonesia memang sudah tergolong cukup tinggi dan berbagai perusahaan e-wallet juga berlomba untuk menjadi pemimpin dalam penyediaan jasa pembayaran digital.) Electronic payment ini harus bisa dipercaya akan keamanannya dan juga harus bisa memudahkan aktivitas manusia dalam menggunakannya.Penelitian ini bertujuan untuk mengetahui pengaruh pemasaran media sosialdan kepercayaan merek terhadap customer brand engagement (studi kasus pengguna elctronic payment). Teori yang digunakan adalah teori komunikasi pemasaran, sosial media, kepercayaan merek, dan keterlibatan konsumen. Penelitian ini menggunakan metode kuantitatif. Teknik pengumpulan data yang digunakan yaitu dengan menggunakan kuesioner. Cara yang digunakan adalah menyebarkan kuesioner melalui google form dengan menyebarkan secara online kepada orang yang pernah menggunakan electronic payment. Populasi dari penelitian ini adalah pengguna electronic payment dan sampel yang digunakan berjumlah 100 sampel. Hasil dari penelitian ini adalah Pemasaran Media Sosial dan Kepercayaan Merek mempunyai pengaruh terhadap customer brand engagement dalam pengguna electronic payment.